Coarse Resolution Defect Localization Algorithm For An Automated Visual Pcb Inspection - Ibrahim, Zuwairie (Penerbit UTM Press, 2002)
One of the backbones in electronic manufacturing industry is the printed circuit board (PCB) manufacturing. Current practice in PCB manufacturing requires an etching process. This process is an irreversible process. Printing process, which is done before the etching process, caused most of the destructive defects found on the PCB. Once the laminate is etched, the defects, if exist would cause the PCB laminate to become useless. Due to the fatigue and speed requirement, manual inspection is ineffective to inspect every printed laminate. Therefore, manufacturers require an automated system to detect the defects online which may occur during the printing process. The defect is detected by utilizing wavelet-based image difference algorithm. Hence, this paper proposes an algorithm for an automated visual PCB inspection that is able to automatically locate and extract any defect on a PCB laminate. The algorithm works on the coarse resolution differenced image in order to locate the defective area on the fine resolution tested PCB image.